2013
DOI: 10.1215/00031283-2346825
|View full text |Cite
|
Sign up to set email alerts
|

THE DEVELOPMENT OF Children’s USE OF DISCOURSELIKEIN PEER INTERACTION

Abstract: this article examines the use of like as a discourse marker and discourse particle in the spontaneous speech of children age 3-10. Data come from recorded interactions between same-sex peers. Discourse like appeared in the speech of children as young as age 4. Young children used like primarily as a discourse particle preceding determiner phrases. Like was observed in a greater number of syntactic positions as speakers' ages increased and began to appear in different syntactic positions in approximately the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…(4) "Can this be a trip coming up or something… like in the future?" 1991; Miller & Weinert, 1995;Odato, 2013;Siegel, 2002;Underhill, 1988), but to our knowledge there are no studies examining its use by autistic speakers. The current research has addressed this gap by examining like use, overall, and like subtypes by older autistic children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) "Can this be a trip coming up or something… like in the future?" 1991; Miller & Weinert, 1995;Odato, 2013;Siegel, 2002;Underhill, 1988), but to our knowledge there are no studies examining its use by autistic speakers. The current research has addressed this gap by examining like use, overall, and like subtypes by older autistic children.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, discourse markers fill pauses, aid in word-finding, relay uncertainty, and hold one's conversational turn by indicating that the speaker is making an intra-turn pause (Brennan & Schober, 2001; Goodwin & Goodwin, 1986; Irvine et al, 2016; Maclay & Osgood, 1959; Swerts, 1998). Although like is often left out of discourse marker research (Crible, 2017; Geelhand et al, 2020; Kyrstzis & Ervin-Tripp, 1999), analyses of like use show that the pragmatic information it encodes is not represented by other discourse markers, and, correspondingly, speakers use discourse marker like contrastively to others (Fox Tree, 2007; Odato, 2013). Specifically, like is used to convey four different messages about upcoming speech: looseness, focus, quotation, and revision.…”
Section: Like As a Discourse Markermentioning
confidence: 99%
“…Interactional approaches have found that young children can interpret and produce speech styles that change according to gender and social power, for instance by altering their pitch, word choices, clause structure, and level of indirectness, depending on the role they are playing (e.g. Andersen, 1990; Cook-Gumperz & Scales, 1996; Odato, 2013; Shatz & Gelman, 1973). Bilingual children aged 2–3 years use the same kinds of linguistic strategies to repair conversational breakdowns as do monolingual speakers of one of the languages (Comeau, Genesee, & Mendelson, 2010).…”
Section: Children’s Bilingual Language Differentiation and Developingmentioning
confidence: 99%
“…Labov 2001; Tagliamonte 2012). Recent studies by Odato (2010Odato ( , 2013 show that LIKE -although infrequent -can be detected in the speech of four-year-olds and that pragmatic functions and syntactic contexts do not emerge simultaneously: in fact, the developmental pathway of LIKE mirrors its diachronic development. Furthermore, children's grammar of LIKE differs from adult grammars in that the marker is more frequent among adults while the particle is more frequent among young children -only during early adolescence does the pattern begin to mirror adult use.…”
mentioning
confidence: 99%